ANALYTICAL AND NUMERICAL DESCRIPTION OF THE SETTLING PROCESS IN THE ACTIVATED SLUDGE OPERATION - Diehl, Stefan; Sparr, Gunnar; Olsson, Gustaf (Instrumentation, Control and Automation of Water and Wastewater Treatment and Transport Systems, 1990)
The secondary clarifier or settler is crucial for the whole activated sludge operation. Consequently it is important to obtain a reliable analytical model as well as a useful numerical method, which can be used in automatic control of the settling process. Discontinuities (shocks) appear physically, and an analytical description as well as a stable numerical algorithm must be able to handle these discontinuities. A model based on the Kynch theory of sedimentation is used, where the settling flux is a function only of the local concentration and is assumed to have one inflexion point. For such non-convex flux functions the settling process is qualitatively the same, independent of further assumptions on the shapes of the settling functions. Using the theory of non-linear conservation laws, the main results obtained are:•how to calculate transient and asymptotic behaviour;•how to control the concentration profile of the settler, in particular the depth of the sludge blanket, for a given load;•a numerical algorithm which automatically preserves shocks and gives the physically correct solution according to the analytical treatment. The algorithm can be applied on any flux function (with more than one inflexion point).